To simplify the expression:
3^2 x 3^-1 / 5^-2 x 2^0
Firstly, let's simplify the exponents:
3^2 = 3 * 3 = 9
3^-1 = 1/3
5^-2 = 1/5^2 = 1/25
2^0 = 1
Now, substitute these values back into the expression:
9 * (1/3) / (1/25) * 1
Next, let's combine the fractions by multiplying the numerators and denominators:
(9/1) * (25/1) * (1/3)
Multiplying the numerators gives us:
(9 * 25 * 1) / (1 * 3)
Which simplifies to:
225 / 3
Finally, dividing 225 by 3 gives us the answer:
75
simplify- 3^2 x 3^-1/ 5^-2 x 2^0
1 answer